A preliminary qualitative study of nurses' and dietitians' views on malnutrition management and oral nutritional supplementation prescription in the community. (2020) - Castro, Patricia Domínguez; Kennelly, Sharon; Murrin, Celine; Bradley, Catriona; Clyne, Barbara; Bury, Gerard; Finnigan, Karen; McCullagh, Laura; Barry, Michael; Browne, Sarah; Reynolds, Ciara; Bardon, Laura; et al.
Abstract: Protein-energy malnutrition, or undernutrition, arising from a deficiency of energy and protein intake, can occur in developed countries both in hospitalised patients and in the primary care/community setting. Oral nutritional supplements (ONS) are an effective method of managing malnutrition if prescribed for patients who are malnourished or at risk of malnutrition. Pooled data of older adults at risk of malnutrition indicate that ONS combined with dietary counselling is the most effective intervention. Previous Irish research has demonstrated that management of patients 'at risk' of malnutrition in the primary care/community setting is sub-optimal, with low awareness of the condition and its management among non-dietetic health care professionals. Therefore, the aim of this qualitative study is to explore community nurses' and dietitians' experiences and opinions on the management of malnutrition and the prescription of ONS in the primary care/community setting in Ireland. Three focus groups were conducted with primary care dietitians (n = 17) and one focus group with community nurses (n = 5), one of the nurses had prescribing rights. The focus groups explored the following domains; the term malnutrition and patient population presenting as malnourished or at risk of malnutrition, barriers and facilitators in the management of malnutrition, ONS prescribing in the primary care/community setting, and future directions in the management of malnutrition and ONS prescribing. Recorded focus groups were transcribed and analysed using inductive thematic analysis. Both professional groups showed similar perspectives, and three preliminary main themes were identified; i) Malnutrition is a misunderstood term, ii) Delayed treatment of malnutrition, iii) Challenges with ONS prescription in the primary care/community setting. Both dietitians and community nurses agreed that the term malnutrition had negative connotations for patients and preferred not to use it with them. Dietitians identified the need for a multidisciplinary approach to manage patients at risk of malnutrition in the community, and community nurses agreed on their pivotal role identifying the risk of malnutrition and providing first line advice to clients. However, community nurses expressed the urgent need for training to provide first line advice to patients to improve their nutritional status to prevent malnutrition. Both groups also agreed on the need for access to more dietitians in the community, and suggested that giving dietitians prescribing rights would improve appropriate ONS prescribing. Community nurses identified a gap in their knowledge of the different ONS products, and the need to receive independent generic education on nutritional supplements.